The issue of formal requirements for supervisory board members in companies co-owned by the State Treasury exemplified by Polska Grupa Zbrojeniowa S.A. (Economic and Political Thought, 2017)
The article presents comprehensive and detailed deliberations of the issueof formal requirements for members of supervisory boards of companies coownedby the State Treasury. The research method used is a case study ofPolska Grupa Zbrojeniowa S.A. (diagnosis of chosen processes taking place inthe company PGZ S.A.), supplemented with a detailed analysis of legal regulationsin force, a review of literature and court decisions, as well as a discussionof documents including earlier opinions presented by public authorities intheir answers to MPs’ queries concerning problems strictly related to previousmethods of selecting candidates to senior management posts in companiesowned by the State Treasury. The first part of the article presents issues oforganizational-legal aspects in the context of methods of selection and formalcriteria for members of the supervisory board of PGZ S.A. With reference tothe discussed topic, answers to important questions related to several chosenimportant narrow research issues are given. Particular attention has been drawnto identification and objective discussion of the importance of relevant legalpremises, which predetermine differentiated formal requirements for membersof supervisory boards in companies co-owned by the State Treasury. Additionally,the author comments on the latest amendments to the regulations in forceconcerning bans and limitations on the accumulation of positions by membersof supervisory boards of companies co-owned by the State Treasury from theperspective of corporate governance mechanisms in PGZ capital group.